Effect of milling on the perovskite phase formation of Pb(Mg1/3Nb2/3)O3using the starting precursors PbO and MgNb2O6 - A. Chaipanich (2018)
Lead magnesium niobate, Pb(Mg1/3Nb2/3)O3(PMN) was produced using the columbite method and the effect of milling on the formation of the perovskite phase of Pb(Mg1/3Nb2/3)O3was investigated. Columbite, MgNb2O6, was ball milled with PbO for 24, 48, 72 and 96 h before calcining at 650-750 °C for 2 h. The average particle size was found to be reduced from 4.26 μm (at 24 h) to 1.05 μm after milling for 96 h. For a given calcination temperature, more perovskite phase and less impurities were detected by X-ray diffraction in samples milled for longer times compared to the conventional 24-h milling. These results agree with the differential analysis observation that less heat is evolved in the longer-milled samples, suggesting the heat energy required for the PMN reaction is less in these samples compared to the sample milled for only 24 h. © 2005 Elsevier B.V. All rights reserved.